Multiple Structures Disclose the Secretins' Secrets - Filloux, Alain (J Bacteriol, 2018)
Bacterial secretins are outer membrane proteins that provide a path for secreted proteins to access the cell exterior/surface. They are one of the core components of secretion machines and are found in type II and type III secretion systems (T2SS and T3SS, respectively). The secretins comprise giant ring-shaped homo-oligomers whose precise atomic organization was only recently deciphered thanks to spectacular developments in cryo-electron microscopy (cryo-EM) imaging techniques.